Masculinities at Stake Under the Migratory Experience of Former Braceros of Telchac Pueblo, Yucatan - Be Ramírez, Pedro Antonio (2019)
This article analyzes the experiences that the men from Telchac Pueblo, Yucatan, elaborate on their masculinities as a result of their incursion as agricultural workers in the Bracero Program (1942-1964), proposed between Mexico and United States. Through an ethnographic study with in-depth interviews, dialogues with key informants, and participant observation carried out at the place of origin, this article examines the narratives of the Telchac men on their experience as providers, as adventurous and daring, but also –especially during the las years of this bi-national program— as disposable, useless and worthless men. The text concludes with some reflections on the ways in which patriarchal hegemony operates in the bodies, beliefs, and forms of relationship between the Telchac men and their families; where the conventional masculinity glides between physical, social and/or symbolic borders.